Synthesis and characterization of new pH- and thermo-responsive hydrogels based on N-isopropylacrylamide and 2-oxazolines - Campos Dávila, Estuardo Job (2021)
New pH- and thermo-responsive hydrogels (HG) were synthesized by free radical polymerization of N-isopropylacrylamide and a macromonomer, which was a hydrolyzed random copolymer of 2-carboxyethyl- and 2-methyl-2-oxazoline, using a bisacrylamide as crosslinker. The polymerization was carried out in a mixture of water and ethanol at room temperature and was initiated by ammonium peroxodisulfate. The HG showed conformational transitions with variation of temperature and/or pH-value and as a function of hydrogel composition. This property was shown macroscopically as hydrogel contraction or expansion. The HG structures were characterized by high-resolution magic angle spinning (HRMAS) NMR spectroscopy. The thermal properties, in particular the lower critical solution temperatures, were determined by temperature-dependent HRMAS NMR measurements and differential scanning calorimetry. The pH responsibility was determined by swelling experiments in water at different pH values.